IMPACT OF DIGITAL BANKING ON BROADENING INVESTMENT ACCESS: BASIS FOR ENHANCED FINANCIAL DECISION-MAKING PLAN - Acezel Manlapaz, Mark; Quendangan, Erwin; Jose H. Leyba, Ceazar (Penerbit Lafadz Jaya, 2024)
The advent of digital banking has ushered in a transformative era in the financial services industry, significantly broadening access to investment opportunities and reshaping financial decision-making processes. This research investigates the impact of digital banking on expanding investment access and its implications for enhanced financial decision-making practices. Through a comprehensive review of existing literature and analysis of primary data, this study examines the mechanisms through which digital banking platforms facilitate investment access for diverse demographic groups and geographical regions. Moreover, it explores the role of digital banking technologies in empowering individuals with tools for informed decision-making, risk management, and portfolio diversification. Employing a descriptive methodology, data were collected from 100 respondents via structured questionnaires and supplemented by random interviews with employees, and clients. Statistical techniques such as percentage, weighted mean, Likert scale, ANOVA and ranking were used for data analysis. Key findings highlight the profound influence of digital banking on democratizing investment participation, reducing barriers to entry, and promoting financial inclusion. Furthermore, the study elucidates the potential benefits and challenges associated with the adoption of digital banking in optimizing investment strategies and fostering financial literacy among consumers. By knowing the transformative effects of digital banking on investment accessibility and decision-making dynamics. This research contributes to the evolving discourse on financial innovation and its implications for inclusive economic growth in the digital age. The study provided several recommendations. These included Enhancing digital platforms, Diversifying investment options, Educational initiatives, Security measures, Geographic inclusivity, Transaction cost reduction, and Regular communication.